Determining the Nature of IC 10 X-2: A Comprehensive Study of the Optical/IR Emission from an Extragalactic BeHMXB - Jwaher Alnaqbi; Joseph D. Gelfand; Payaswini Saikia; Craig Heinke; M. C. Baglio; David M. Russell; Guobao Zhang; Antonios Manousakis; Ivan Yu. Katkov; Fraser Lewis (The Astrophysical Journal)
We present a comprehensive analysis of the optical and infrared (IR) properties of high-mass X-ray binary (HMXB) IC 10 X-2, classified as a supergiant HMXB and superfast X-ray transient by previous work. Our analysis of regular (daily and weekly) observations by both the Zwicky Transient Facility and Las Cumbres Observatory over a 5 yr period indicates both periodic flares and variations in the apparent magnitude and color with a period of ∼26.5 days—likely the orbital period of this binary system. The periodic flaring suggests the stellar companion is a Be star, with flares resulting from increased accretion onto the neutron star (NS) when it enters the stellar decretion disk. The periodic variations in the optical/IR brightness and color likely result from orbital variations in the hydrogen column density along the line of sight or a transient accretion disk around the NS. Lastly, the numerous short-duration episodes where IC 10 X-2 is significantly “redder” or “bluer” than normal likely result from clumps within this system—which can accrete onto the NS (causing IC 10 X-2 to appear bluer) or pass through the line of sight (causing IC 10 X-2 to appear redder). These results substantially increase our understanding of the evolution of this source, which is a significant source of ionizing photons in its host galaxy IC 10, a low-mass, metal-poor starburst galaxy similar in many respects to those thought to be common in the early Universe.